Association between out-of-hospital cardiac arrest and survival in paediatric traumatic population: results from the French national registry. (5th June 2023) - Lockhart-Bouron, Marguerite; Baert, Valentine; Leteurtre, Stéphane; Hubert, Hervé; Recher, Morgan
Abstract : Background and importance: Trauma is an important cause of paediatric out-of-hospital cardiac arrest (OHCA) with a high mortality rate. Objectives: The first aim of this study was to compare the survival rate at day 30 and at hospital discharge following paediatric traumatic and medical OHCA. The second aim was to compare the rates of return of spontaneous circulation and survival rates at hospital admission (Day 0). Setting and participants: This multicentre comparative post-hoc study was conducted between July 2011 and February 2022 based on the French National Cardiac Arrest Registry data. All patients aged <18 years with OHCA were included in the study. Outcome measures and analysis: Patients with traumatic aetiology were matched with those with medical aetiology using propensity score matching. Endpoint was the survival rate at day 30. Main results: There were 398 traumatic and 1061 medical OHCAs. Matching yielded 227 pairs. In non-adjusted comparisons, days 0 and 30 survival rates were lower in the traumatic aetiology group than in the medical aetiology group [19.1% vs. 24.0%, odds ratio (OR) 0.75, 95% confidence interval (CI) 0.56–0.99, and 2.0% vs. 4.5%, OR 0.43, 95% CI, 0.20–0.92, respectively]. In adjusted comparisons, day 30 survival rate was lower in the traumatic aetiology group than in the medical aetiology group (2.2% vs. 6.2%, OR 0.36, 95% CI, 0.13–0.99). Conclusion: In this post-hoc analysis, paediatric traumatic OHCA was associated with a lower survival rate than medical cardiac arrest.